Ukuran Kelompok Monyet Ekor Panjang (Macaca Fascicularis) Di Hutan Desa Cugung Kesatuan Pengelolaan Hutan Lindung Gunung Rajabasa Lampung Selatan - Angga Pramudya; Agus Setiawan; Elly Lestari Rustiati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Gunung Rajabasa is in register 3, under Kesatuan Pengelolaan Hutan Lindung (KPHL, Management Unit of Protected Trees) Gunung Rajabasa. Cugung is village under KPHL Gunung Rajabasa owns a local forest with high diversity, especially long-tailed macaques. Research was conducted in October - November 2014. Habituation was done, concentration count was applied in 4 location its groups size in Cugung is 17-22 individuals. Group composition is 4-5 males, 6-9 females, 1-3 young males, 1-3 young famales and 1-2 infants. Keywords: Local Forest , KPHL Gunung Rajabasa, long-tailed macaques, group size